School inclusion discourses: moralizing ways, humanizing ways - Corrêa Henning, Paula; Lockmann, Kamila (Revista Diálogo Educacional, 2013)
In the present article we intend to put under suspicion some discourses about school inclusion, which we have seen circulating nowadays. To do this we selected some editions of the magazine Nova Escola presenting school inclusion as central theme of their articles. Discourses marked by terms like “love”, “donation”, “affection”, and “humanization” are examined in this paper from the theoretical basis found in Friedrich Nietzsche, which allows us denaturalize the benevolent air announced in those narratives. We must be open to Others in order to be touched, if those who are touching us conspire in favor of goodness and order. We also problematize the emphasis those discourses show in socializing and conviviality processes. They mark a kind of learning trivialization since they reiterate that conviviality with others; respecting rules and knowing how to behave are fundamental apprenticeships in inclusion processes. By putting those discourses under exam, the text aims to provoke thinking and to dismiss approved truths about school inclusion pronounced by modernity.